2015
DOI: 10.1186/s12968-015-0198-x
|View full text |Cite
|
Sign up to set email alerts
|

Time course of cardiometabolic alterations in a high fat high sucrose diet mice model and improvement after GLP-1 analog treatment using multimodal cardiovascular magnetic resonance

Abstract: BackgroundCardiovascular complications of obesity and diabetes are major health problems. Assessing their development, their link with ectopic fat deposition and their flexibility with therapeutic intervention is essential. The aim of this study was to longitudinally investigate cardiac alterations and ectopic fat accumulation associated with diet-induced obesity using multimodal cardiovascular magnetic resonance (CMR) in mice. The second objective was to monitor cardiac response to exendin-4 (GLP-1 receptor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 93 publications
3
29
1
1
Order By: Relevance
“…Several factors such as myocardial lipid accumulation and lipotoxicity may contribute to the increased cardiac fibrosis observed in the mice fed a high-fat diet. A recent study by Abdesselam et al [50] showed increased myocardial lipid accumulation along with increased cardiac fibrosis in mice fed a high-fat and high-sucrose diet. Furthermore, Glenn et al [44] showed increased cardiac fibrosis in a mouse model of cardiac steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors such as myocardial lipid accumulation and lipotoxicity may contribute to the increased cardiac fibrosis observed in the mice fed a high-fat diet. A recent study by Abdesselam et al [50] showed increased myocardial lipid accumulation along with increased cardiac fibrosis in mice fed a high-fat and high-sucrose diet. Furthermore, Glenn et al [44] showed increased cardiac fibrosis in a mouse model of cardiac steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple animal studies have shown beneficial effects of GLP‐1 RAs on ectopic fat development. In mice, they have been shown to decrease myocardial steatosis and fibrosis, to improve myocardial function and perfusion, and to decrease hepatic steatosis . These effects were shown to be both indirect, through benefit on weight loss and glycaemic improvement, and direct, through the activation of the GLP‐1 receptor, modulating key elements of the insulin signalling pathway, lipid peroxidation (oxidative stress) and hepatic de novo lipogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Exendin-4 or liraglutide has been shown to reduce the occurrence and degree of hepatic steatosis independent of their action on body weight [47]. These effects were observed in experimental animals but also in the clinical setting.…”
Section: Effect Of Glucagon-like Peptide-1 To Improve Hepatic Steatosismentioning
confidence: 74%